2022
DOI: 10.3390/ijerph192214801
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Differentiation and Driving Forces of Ecological Welfare Performance in the Yangtze River Economic Belt

Abstract: Ecological welfare performance contributes directly to human well-being and regional sustainable development. Improving the regional ecological welfare performance in the process of pursuing green and sustainable development demands theoretical innovation and empirical exploration. Based on the super-efficiency SBM model, this study evaluated the ecological welfare performance of 108 cities during the period of 2009 to 2019. The Dagum Gini coefficient decomposition and spatial convergence model were employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Scholars have reached different conclusions on the impact of industrial structure on ecological well-being performance. From the current findings, scholars generally agree that the increase in the share of tertiary industry has a catalytic effect on ecological well-being performance [24]. Hu et al [25], based on city-level data from 2001-2017 in the Yangtze River Delta region, showed that the optimization of industrial structure has a significantly positive effect on the improvement of ecological well-being performance.…”
Section: Industrial Structure and Well-being Performancementioning
confidence: 59%
“…Scholars have reached different conclusions on the impact of industrial structure on ecological well-being performance. From the current findings, scholars generally agree that the increase in the share of tertiary industry has a catalytic effect on ecological well-being performance [24]. Hu et al [25], based on city-level data from 2001-2017 in the Yangtze River Delta region, showed that the optimization of industrial structure has a significantly positive effect on the improvement of ecological well-being performance.…”
Section: Industrial Structure and Well-being Performancementioning
confidence: 59%
“…Four indicators are chosen to investigate the influencing factors of coupling and coordinated development, considering both internal and external aspects in alignment with existing studies. Among these, city scale: City_S , the number of urban population, the higher the proportion of urban population, the larger the city 22 ; Industrial structure upgrading: Ind , the level of advanced industrial structure, the higher the proportion of tertiary industry indicates the industrial structure 23 ; Economic development: Econ , per capita GDP, the level of economic development is represented by per capita GDP after adjustment; Green technology innovation: Gtec , the number of authorized green invention patents, the higher the proportion of green invention patents, the higher the green technology innovation ability 11 .…”
Section: Results and Analysismentioning
confidence: 99%
“…Similarly, employing the Super-SBM model, Yao et al evaluated ecological welfare performance across Chinese provinces and municipalities, emphasizing the necessity to enhance resource use efficiency and environmental regulation 20 . Ecological welfare performance is influenced by various factors including urbanization 21 , industrial structure 22 , technological innovation 23 , and green finance 24 . Among these, urbanization stands out as a primary determinant shaping ecological welfare performance.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, things that are near together have a stronger association than things that are far apart. Geographical autocorrelation quantifies the degree of geographic relationship between geographical objects and the attribute values associated with them (Zhao et al, 2021) (Bai et al, 2022). Below are the formulas for determining Moran's I.…”
Section: Spatiotemporal Characteristics Of the Supply Demand Ratio (Sdr)mentioning
confidence: 99%
“…Ecosystem services (ES) refer to advantages that individuals gain from ecosystems, such as provision, regulation, support, and cultural services (Bai et al, 2022). In the past few years, there has been a notable rise in the integration of ecosystem services, specifically those related to water resources, into global decisionmaking processes (Cabral et al, 2021).…”
Section: Introductionmentioning
confidence: 99%